2021
DOI: 10.3389/fgene.2021.774010
|View full text |Cite
|
Sign up to set email alerts
|

Potential Prognostic Value of a Seven m6A-Related LncRNAs Signature and the Correlative Immune Infiltration in Colon Adenocarcinoma

Abstract: Long non-coding RNAs (lncRNAs) and their N6-methyladenosine (m6A) modifications play an essential role in tumorigenesis and cancer progression. This study was designed to explore the value of m6A-related lncRNAs in prognosis and therapeutic applications of immune infiltration of colon adenocarcinoma (COAD). We downloaded the COAD gene expression and clinical data from The Cancer Genome Atlas project. By co-expression analysis, Lasso Cox regression analysis, and univariate and multivariate Cox regression, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the overall cohort ( Figure 6G ), the RMlnc-score (our study) had an AUC of 0.737 at 5-years overall survival, which was substantially higher than ChaiLncSig (AUC = 0.653), YunLncSig (AUC = 0.658), and ZhangLncSig (AUC = 0.659). This suggests that the RMlnc-score has higher accuracy in predicting survival compared to three recently published lncRNA signatures for colon cancer ( Chai et al, 2021 ; Yun and Yang, 2021 ; Zhang et al, 2021d ). The survival status and RMlnc-score score curves for the training and test sets showed ( Figure 6H, I , 7I) that RMlnc-score was proportional to the number of deaths in CC patients.…”
Section: Resultsmentioning
confidence: 83%
“…In the overall cohort ( Figure 6G ), the RMlnc-score (our study) had an AUC of 0.737 at 5-years overall survival, which was substantially higher than ChaiLncSig (AUC = 0.653), YunLncSig (AUC = 0.658), and ZhangLncSig (AUC = 0.659). This suggests that the RMlnc-score has higher accuracy in predicting survival compared to three recently published lncRNA signatures for colon cancer ( Chai et al, 2021 ; Yun and Yang, 2021 ; Zhang et al, 2021d ). The survival status and RMlnc-score score curves for the training and test sets showed ( Figure 6H, I , 7I) that RMlnc-score was proportional to the number of deaths in CC patients.…”
Section: Resultsmentioning
confidence: 83%
“…With the advances in high-throughput sequencing technology, more and more studies have published different kinds of RNA modification including the internal mRNA m7G methylation. In clinical research, several previous studies identified the role of N6-methyladenosine (m6A) remodeling in the molecular pathogenesis of several types of carcinogenesis and the role of m6A-related genes in the prognosis of several types of cancers ( Chai et al, 2021 ; Jin et al, 2021 ; Han et al, 2022 ). M6A remodeling has been well studied in HCC as some studies have identified m6A related gene signature model for the prediction of HCC ( Jin et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the two groups were assessed using t -tests (for normally distributed data) or Mann–Whitney tests (for non-normal distribution), and p < 0.05 was considered statistically significant. The relationships between risk score and drug sensitivity were determined by the Spearman’s correlation analysis [ 14 ]. p values were two-sided and all data with p < 0.05 were recognized as statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…They play a key role in various cellular processes in the cancer disease process [ 11 , 12 , 13 ]. Numerous studies have shown that lncRNAs can be involved in colon adenocarcinoma progression and immunotherapy through various pathways, such as m6A [ 14 ], ferroptosis [ 15 ], necroptosis [ 16 ], and autophagy [ 17 ]. In contrast, the value of the cuproptosis-related lncRNA prognostic model in colon adenocarcinoma has not received attention.…”
Section: Introductionmentioning
confidence: 99%